Verifying the Truth on Their Own Terms - Murat Balıkçıoğlu, Efe (Knowledge Hegemonies in the Early Modern World, 2023)
The present volume offers a detailed analysis of a fifteenth-century court debate on God’s unicity (tawḥīd), involving the Ottoman scholars Mollā Zeyrek (d. 903/1497-98 [?]) and Ḫocazāde Muṣliḥuddīn Muṣṭafā (d. 893/1488), as a chance to highlight the dynamics of knowledge production at the time: in post-classical Islamic scholarship, an essential element of the process was scholars’ adroitness in synthesizing arguments from differing schools of philosophy and theology – via close readings of past masters. This dialectic unfolded during a period of imperial restructuring, at a time when Sultan Meḥmed II (d. 886/1481) realized his cosmopolitan and universalistic ambitions through his persistent patronage of philosophy and science, a case that is illustrated by his glorious palatine library. The setting, audience, and format of the debate, along with the analyses reveal that the production of knowledge in the early modern Islamic world was intricate, vibrant, and dynamic – not stale or derivative as previously thought. This book attempts at reconstructing the debate through the information found in bio-bibliographical sources, and comments on certain social and cultural aspects of the fifteenth-century Ottoman scholarship. Analyses of lemmata in the plethora of commentaries and glosses reveal that Ottoman scholars could posit numerous and disparate doctrinal positions, each referencing specific texts, through which the scholars gave their own syntheses based on their unique perspectives. This method of scholarly arbitration is called ‘verification’ (taḥqīq) and is exemplified here in Ḫocazāde’s defense and recontextualization of Avicennan philosophy in early Ottoman philosophical theology. The court debate at hand concerns Avicenna’s often-contested ontological formulation, which equaled God’s quiddity/essence to His existence and necessity, a view that went against the theological principle of God’s singularity according to a tradition of Muslim theologians. Ḫocazāde’s defense of the philosophers’ proof demonstrated that one of the senses of the ontological term ‘necessity’ that Avicenna put forth was identical to God’s quiddity/essence, as well as His ‘pure existence’. Having gained the upper hand in the debate by verifying Avicenna’s thesis, Ḫocazāde’s argumentative efforts proved that not only could the philosophers’ claim be reconciled with post-classical Islamic theology, but this proof also held true on their own terms despite Zeyrek’s (and the theologians’) objections.